Numerical Investigation of the Cooling Behavior of Molded Chocolate Products. Issue 10 (5th September 2022) - Lörcher, Marc; Behrens, Stefan; Böttger, Arne; Lange, Claudia; Schräer, Christian; Luo, Xing; Kabelac, Stephan
Abstract: In addition to taste and melting behavior, the gloss is an important quality criterion of chocolate products. Differences considering the gloss on products can be attributed to different causes in the production process. The chocolate which has been precrystallized by shearing and supercooling is further cooled, crystallized, and transported as a solid chocolate out of the cooling process. The cooling of the chocolate is largely unexplored in a paternoster refrigerator. Therefore, the resulting flow profile and temperature profile are numerically studied in this work. Abstract : Chocolate cooling in polycarbonate molds flowed by air is simulated. In a model with constant wall temperature, the flow profile around the mold is calculated and used to determine the transient cooling process of the chocolate in the mold. With specific heat capacities found by differential scanning calorimetry, the transient cooling process of milk chocolate can be validated with deviations of less than 1 K.